PHYSICAL AND ORGANOLEPTIC CHARACTERISTICS OF TAMARIND PASTE (Tamarindus Indica L) WITH MODIFIED ELEPHANT CASSAVA (Manihot Esculenta) DERIVATIVE PRODUCT THICKENER - Rahayu, Putri Nanda; Prabowo, Sulistyo; Rachmawati, Maulida (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2024)
This research was conducted to determine the effect of physical properties on elephant cassava derivative products as a thickener for tamarind paste. This study used a non-factorial completely randomized design (CRD) with 2 treatments, namely types of thickener (modified starch and mocaf) at 5 different concentrations (0%, 1%, 3%, 5%, and 10%) with 3 repetitions. The addition of 10% elephant cassava mocaf flour had the highest value based on the viscosity test with a value of 5624 mPas, in the 10% solubility test the addition of modified starch has a value of 90.47%, the speed with heating at 80℃ ranges from 45-66 seconds and the organoleptic test for taste attributes is 2.04- 2.48.